(untitled) (Conferencea, 2023)
Today, great importance is attached to the development of knowledge of which developed countries of the world do not receive, in the field of education, especially a foreign language from school age, in addition to mathematics. In our country, great attention is paid to the presence of eleven more years of Secondary Education and the establishment of Educational Centers for the purpose of vocational guidance in it, as well as the artistic and aesthetic education of young people studying in academic lyceums, vocational colleges, higher education institutions.